Pretty ugly : a Toon book - Sedaris, David (TOON Books, 2024)
"In this hilarious illustrated fable, Anna Van Ogre loses her lovely monstrous looks and is turned into a sickeningly adorable, rosy-cheeked little girl. It starts her on a journey to learn an unforgettable lesson about true beauty"--